Effects of Heat Stress on Mating Behavior and Colony Development in Bombus terrestris (Hymenoptera: Apidae) - Przybyla, Kimberly; Michez, Denis; Zambra, Ella; Anselmo, Abigaël; Hennebert, Elise; Rasmont, Pierre; Martinet, Baptiste (Frontiers in Ecology and Evolution, 2021)
Climate change is related to an increase in the frequency and intensity of extreme events such as heatwaves. In insect pollinators, heat exposure is associated with direct physiological perturbations, and in several species, could lead to a decrease of fitness related to a decrease in fertility. Here we developed a new experimental protocol in controlled conditions to assess if the exposure to high temperatures could modify the attractiveness and fertility of Bombus terrestris males. Our results show that virgin queens of B. terrestris do not have preferences between the pheromonal secretions of heat-exposed and control males. Moreover, mating with a heat-exposed male has no impact on the copulation behavior and the development of the nest (brood composition). We advise to extend trials to cover a range of wild and heat-sensitive species on multiple generations to better understand the impact of heat waves on the bumblebee communities.